Saturable binding of halothane to rat brain synaptosomes. - el-Maghrabi, E A (1992)
The hypothesis that volatile anesthetics act directly on or bind specifically to membrane proteins remains controversial. In earlier in situ electron probe microanalysis studies in cardiac muscle we showed preferential partitioning of halothane into mitochondria. To determine whether partitioning represents saturable binding or simple solubility, a photoaffinity labeling method was developed for halothane to examine binding in rat brain synaptosomes. Radioligand binding assays were then used to determine binding parameters for this important inhalational anesthetic. UV-light exposure of synaptosomes incubated with clinical concentrations of [14C]halothane resulted in sufficient labeling to allow characterization of binding sites. Analysis of saturation and competition curves showed that greater than 60% of [14C]halothane photolysis product binding to synaptosomes was specific, with low affinity (Kd = 0.49 +/- 0.16 mM) and high binding site concentration (Bmax = 1.87 +/- 0.75 nmol/mg of protein). Halothane photoaffinity labeling was partially inhibited by isoflurane (20%), chloroform (44%), 2-bromotrifluoroethane (20%), and dichlorotrifluoroethane (20%) but not by ethanol. The Kd measured with this photoaffinity approach is similar to the concentration of halothane required to produce anesthesia in rats.